Asia bond monitor. (Metro Manila, Philippines Asian Development Bank, 2017)
Emerging East Asia has shown signs of improving economic growth and rising inflation and a decline in LCY government bond yields was seen in most markets given improving investor confidence. The improved outlook could also strengthen emerging East Asias financial markets against the possible reversal of capital flows in response to the Federal Reserves expected monetary policy normalization. The notable exception to the regional trend of declining yields was the Peoples Republic of China, where 2 year and 10 year yields rose between 31 December and 15 February as the Peoples Bank of China engaged in tightening measures to protect against asset and credit risks.
Keywords: Asia -- Economic integration; Sustainable development; Electronic books